The Use of Integrative Therapies in Patients with Amyotrophic Lateral Sclerosis in Shanghai, China. (2nd December 2013) - Pan, Weidong; Chen, Xiangjun; Bao, Jie; Bai, Yu; Lu, Hua; Wang, Qiudong; Liu, Yi; Yuan, Canxing; Li, Wenwei; Liu, Zhenguo; Liu, Jun; Zhu, Xuying; et al.
Abstract : Objective . To investigate the current use of integrative therapies (IT) in the treatment of patients with amyotrophic lateral sclerosis (ALS). Methods . A cross-sectional, multicenter clinical epidemiological survey was conducted in 12 hospitals in Shanghai. We investigated the type and frequency of IT use and determined whether the use of IT correlated with demographic, social, or disease-specific characteristics in our patient population. Results . A total of 231 (89.5%) of 258 patients with ALS were eligible for the study and 229 (99% of all) of 231 reported the use of at least one IT for the treatment of ALS. Vitamins and Chinese herb decoctions, Chinese herb compounds, massage therapy, and acupuncture were the 5 most commonly used therapies. There was a strong association between education level, income, and use of IT. A household income of more than 75, 000 RMB (49, 995) correlated with multiple IT use, and married patients used IT more often than single individuals. The main reasons for using IT were to treat weakness and fatigue, muscle atrophy, the development of ALS, depression, insomnia, limb pain or numbness, and side effects associated with Riluzole. Conclusion . The use of IT is common in patients with ALS in Shanghai. Vitamins and TCM are the most used additional therapies and the widespread and largely unexamined use of IT for ALS requires more attention.